Contextualizing SDGs by the Means of Vernacular Architecture – The Case of Iran - Salehi, Parnian (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2024)
The contemporary world faces urgent challenges in sustainable development due to escalating urbanization and increased pressure on natural resources, encompassing environmental, economic, and socio-cultural dimensions. Addressing these multifaceted challenges requires a comprehensive approach that integrates sustainable techniques derived from rural contexts and references vernacular architecture while aligning with the Sustainable Development Goals (SDGs). Sustainability, as a concept, acknowledges the interconnectedness of environmental, social, and economic aspects of development. It emphasizes adopting practices that preserve resources, minimize ecological impact, and prioritize community well-being. In rural settings, where reliance on natural resources holds deep cultural significance, tailored sustainable development strategies are imperative. This research examines sustainability through the lens of the UN Sustainable Development 17 Goals (SDGs), categorizing architectural sustainable techniques taken from houses in rural areas and referencing vernacular architecture. Focusing on socio-cultural challenges associated with SDG achievement, the study investigates global rural housing case studies, utilizing qualitative methodologies and extensive literature surveys using two case studies (Volontariat and Magoda project) from SDGs. Special emphasis is placed on Iranian case studies, providing insights tailored to the local context and identifying techniques to meet social, economic, and cultural needs. Vernacular architecture, influenced by geography, climate, and cultural traditions, showcases sustainability, resource efficiency, and minimal environmental impact. This paper analyzes recent literature on vernacular architecture, addressing traditional materials, sustainability, cultural aspects, climate adaptation, and repurposing abandoned structures. It suggests interdisciplinary research and fieldwork in underrepresented regions to integrate contemporary solutions into historic vernacular buildings while meeting modern comfort standards. Vernacular architecture emerges as a key player in sustainable practices, embodying local solutions and cultural adaptation. Integrating vernacular architecture into urban and rural designs has the potential to create environmentally adaptable and culturally appropriate dwellings, fostering a sense of place and cultural continuity. In summary, this thesis significantly analyses sustainable development goals by exploring the integration of vernacular architecture sustainable techniques in rural designs, particularly in the Iranian context. By investigating local and cultural contexts, it aims to propose practical insights and solutions, fostering a more sustainable and culturally sensitive built environment.

ÖZ: Günümüz dünyası, artan kentselleşme ve doğal kaynaklara yönelik artan baskı gibi sürdürülebilir kalkınma konusunda acil zorluklarla karşı karşıya. Bu çok yönlü zorluklara karşı koymak için sürdürülebilir kırsal bağlamdan türetilen teknikleri içeren ve yerel mimariye referans veren kapsamlı bir yaklaşım gereklidir, aynı zamanda Sürdürülebilir Kalkınma Hedefleri (SDG'ler) ile uyumlu olmalıdır. Kavram olarak sürdürülebilirlik, kalkınmanın çevresel, sosyal ve ekonomik yönlerinin birbirine bağlılığını kabul eder. Kaynakları koruyan, ekolojik etkiyi en aza indiren ve toplum refahını öncelikli kılan uygulamaların benimsenmesini vurgular. Doğal kaynaklara olan bağımlılığın derin kültürel önem taşıdığı kırsal ortamlarda, özel olarak uyarlanmış sürdürülebilir kalkınma stratejileri hayati öneme sahiptir. Bu araştırma, BM Sürdürülebilir Kalkınma 17 Hedefi (SDG) bakış açısıyla sürdürülebilirliği inceleyerek kırsal kökenli sürdürülebilir teknikleri kategorize eder ve geleneksel mimariye referans verir. SDG başarısıyla ilişkilendirilen sosyo-kültürel zorluklara odaklanarak, çalışma küresel kırsal konut örneklerini araştırır, nitel metodolojileri kullanır ve iki vaka çalışması (Volontariat ve Magoda projesi) üzerinden geniş bir literatür taraması yapar. Özellikle İran vaka çalışmalarına vurgu yaparak, yerel bağlama özgü içgörüler sunar ve sosyal, ekonomik ve kültürel ihtiyaçları karşılamak için kullanılabilecek teknikleri tanımlar. Coğrafya, iklim ve kültürel geleneklere bağlı olarak şekillenen yerel mimari, sürdürülebilirliği, kaynak verimliliğini ve minimum çevresel etkiyi sergiler. Bu makale, yerel mimari üzerine son literatürü inceleyerek geleneksel malzemeleri, sürdürülebilirliği, kültürel yönleri, iklim adaptasyonunu ve terk edilmiş yapıları yeniden amaçlama konularını ele alır. İnterd disipliner araştırma ve az temsil edilen bölgelerde saha çalışmalarını önerir, böylece çağdaş çözümlerin tarihi yerel binalara entegre edilmesini ve modern konfor standartlarını karşılamayı amaçlar. Yerel mimari, sürdürülebilir uygulamalarda önemli bir rol oynar, yerel çözümleri ve kültürel adaptasyonu temsil eder. Yerel mimariyi kentsel ve kırsal tasarımlara entegre etmek, çevresel adapte olabilir ve kültürel olarak uygun konutlar yaratma potansiyeline sahiptir, böylece bir yerin ve kültürel sürekliliğin hissini geliştirir. Özetle, bu tez, İran bağlamında özellikle SDG'lerle uyumlu kırsal tasarımlarda yerel mimarinin entegrasyonunu keşfederek sürdürülebilir kalkınma söylemine önemli bir katkıda bulunur. Yerel ve kültürel bağlamları inceleyerek, pratik içgörüler ve çözümler önermeyi amaçlar, daha sürdürülebilir ve kültürel duyarlı bir yapı ortamını teşvik etmek.
Master of Science in Architecture. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2024. Supervisor: Prof. Dr. Resmiye Alpar Atun
Keywords: Architecture Department; Sustainability, Sustainable Development Goals (SDGs), Sustainable Design Techniques, Vernacular Architecture, Rural Design, Iran; Sustainable Architecture--Iran; Urban Planning--Urban Policy--Urban Spaces--Design--Vernacular Architecture--Iran